Selection of a priority indicator for assessing the sustainability of the corporation's funding sources by actual and potential stakeholders - V. V. Manuylenko; N. V. Gryzunova; A. I. Khakirov; M. A. Loktionova; G. A. Ermakova (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the study is to develop priority tools for assessing the financial condition of a corporation by different categories of stakeholders, both actual and potential. The study identifies the main areas of financial activity of the corporation from the perspective of actual and potential stakeholders, implements the traditional tools of their assessment by actual stakeholders – owners, financial managers, creditors, landers, investors, suppliers, etc. It is determined that the universal indicator of assessing the financial condition of a corporation for all categories of stakeholders is the stability of its sources of financing in the current and strategic period. As a result, the choice of a priority universal indicator for assessing the sustainability of the corporation's funding sources is justified, which has practical significance for actual and potential stakeholders in conditions of uncertainty and risk.